Analisis Produktivitas Tukang Batu Bata Pada Proyek Pembangunan Asrama Puteri Mandala Wangi 2 di Kota Kendari - Mustahyun, Al; Sunaryo, Sunaryo; Rahmat, La Ode Musa; Sufrianto, Sufrianto (Universitas Sulawesi Tenggara, 2021)
Productivity is one of the fundamental factors that influences the ability of performance in the construction industry. Increased productivity will reduce work time, and will reduce costs, especially labor costs so that the minimum labor cost is obtained (labor costs) to get competitive prices both for auction and implementation. The purpose of this study is to analyze the labor productivity time in completing 1 m2 of masonry bricks and to analyze the productivity value of brick masons in completing work activities in the construction project of the Mandala Wangi 2 female dormitory. The results showed that the time required to complete 1 m2 of brick laying work was 41.13 minutes on average. The productivity of the artisans working on the 1st floor is an average of 1.45 m2/hr. Meanwhile, the productivity of craftsmen working on the 2nd floor is an average of 1.47 m2/hr.